A study of patients discharged from the National Mental Hospital into the Greater Manila Area, their health maintenance, and adjustment to the family and the community - Jael-Santos, Josefina A.
The advances in medical science have brought a new hope to the mentally ill. Due to the widespread use of psycho-pharmacological compounds--known popularly as tranquilizers and anti-depressants--medical science has learned how to control many of the troublesome over symptoms of mental illness just as it has learned to control the symptoms of diabetes through insulin. This control of many of the serious behavior problems of mental illness has meant earlier discharge of mental patients from hospitals. But here the analogy of mental illness to many chronic physical disabilities ends. For while the chronic diabetic patient can remain at home and keep his illness under control except in acute states, the mentally ill patient hardly gets the follow-up, attention, and care that he needs after leaving the hospital, resulting in recurrence of symptoms and the eventual need for rehospitalization. While NMH record of discharge is encouraging, the large percentage of readmissions is a glaring testimony to a missing link in the care of discharge mental patients. The extent of the readmission problem is apparent from the records of the National Mental Hospital which is reaffirmed by the study of L. de Guzman. Many of these patients who fail to adjust on return to their communities could be spared this desolating and discouraging experience. With proper care and guidance to patients and members of their families, the recovered patients could maintain themselves in the community, hold regular jobs, and fulfill responsibilities..."where patients have been seen regularly and treatment consisting of drug therapy, psychotherapy and social therapy and guidance--given as needs arise, the results have been dramatic". While there had been many studies conducted in the United States and other countries which identified the needs of the discharged mental patient in his readjustment to the community, no such study has as yet been made in the Philippines. It is therefore the aim of this study to determine the particular needs of the discharged mental patients in our culture. It is hoped that certain factors can be identified and analyzed and appropriate steps adopted which would contribute to the maintenance of the mental health which has been regained and thus prevent hospital readmission. Factors identified would be useful as a basis for future planning for mental health programs and services; education and training of health professionals; and in helping improve the health care delivery system for the people of the Philippines. Objectives of the Study: More specifically this study seeks to elicit answers to the following questions: 1. What type of activities are engaged in by the patient who has been discharged from the National Mental Hospital? 2. How do members of the family react to the recovered mentally ill member? 3. What facilities for health services are available to the discharged mental patient and, if any to what extent have these facilities been utilized?
Thesis (Doctor of Public Health)--University of the Philippines Manila.
Keywords: Mentally ill -- Rehabilitation; Mentally ill -- Care and treatment